Exercise Interventions Combined With Dietary Supplements in Type 2 Diabetes Mellitus Patients—A Systematic Review of Relevant Health Outcomes - Meuffels, Frederike Maria; Isenmann, Eduard; Strube, Malte; Lesch, Alessio; Oberste, Max; Brinkmann, Christian (Frontiers in Nutrition, 2022)
Introduction Physical training can improve several health variables in patients with type 2 diabetes mellitus (T2DM). A growing body of studies also finds a positive influence of dietary supplement (DS) intake. The aim of this review is to shed light on the possible effects of training interventions combined with DS intake in T2DM patients. Methods A systematic search was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines in the PubMed and BISp Surf databases. Inclusion criteria were defined using the Patient-Intervention-Comparison-Outcome (PICO) scheme. The Physiotherapy Evidence Database (PEDro) scale was used for quality assessment and risk of bias analysis. Results Ten controlled interventional studies with a total number of 643 subjects met the inclusion criteria. These studies investigated the effects of (a) vitamin D (VD), (b) VD + whey protein, (c) polyphenol containing antioxidant capsules, (d) creatine, (e) L-arginine, (f) leucine-rich amino acids, and (g) broccoli sprouts powder. Eight studies investigated effects on one or more of the following health outcomes: body mass index, fat mass, insulin resistance, glycemic control, lipid profile, oxidative stress/antioxidative capacity and/or inflammatory markers/molecules. Five of the studies show clear superior effects of physical training combined with DS intake (supplements a, b, c, e) on some of these variables compared with training only. However, one study indicates that VD intake might attenuate the training effects on triglyceride levels. Another study found that training + VD + whey protein intake increased tumor necrosis factor-α levels in T2DM patients. The effects of training combined with DS intake on renal function (supplement d) or incretin metabolism (supplement a) were investigated in two further studies. These studies do not show any additional effects of DS intake. The quality of the majority of the studies was high. Conclusion DS intake can potentially increase the benefits of physical training for specific health outcomes in T2DM patients. However, negative effects can also be observed. Possible cellular and molecular mechanisms behind potential synergistic or divergent effects of exercise training and DS use in T2DM should be explored in detail in future studies for the development of safe recommendations.